From the Everyday Uses of Twitter and Instagram to Gay Activism in Facebook: the Construction of the Path of a Sociological Investigation Through Online Ethnographic Observations - Kasnik , Jan (Ukrainian Sociological Journal, 2021)
The research into online spaces has been of growing interest for the sociologists. Moreover, the relevance of this field of study has increased even more with the breakout of the COVID pandemics. However, there is still little consensus or a consolidated methodological guidance for beginning searchers concerning the ways of doing an ethnography in such spaces. The goal of this paper is to present some fundamental considerations to have in mind when doing digital ethnography, based on concrete examples from my ongoing master research about the ways of doing gay activism in Facebook by men living in Mexico City. This work is an example of how ethnographic research is a continuous dialogue between our own biases as searchers, the fieldwork observations and theoretical framework. In that sense, the present article offers some guidance for the searchers interested in doing online ethnographic research, concerning its implications for the searchers and the reflexivity of the research participants. In the first section, I demonstrate the vital importance of online ethnographic observations for the precise formulation of the research topic. Then, I show how this fieldwork helped me to reformulate the research to focus only on Facebook. Thirdly, I put emphasis on the importance of our own reflexivity as searchers, an essential component of every inquiry in social science that remains implicit most of the time, giving the mistaken impression that the reflexivity of the searcher is not so important. Indeed, I make the point that the reflexivity of both searchers and participants is instrumental for an in-depth understanding of the research topic and its adequate formulation. Finally, I present very succinctly the different decisions I had to make to personalize my Facebook research profile, as well as the implications of these for the recruitment and the communication with the research participants. In a nutshell, my intention is to contribute to the enriching and still ongoing methodological discussions about the implications of doing online ethnographical research in everyday online spaces such as Facebook.